Contributions to human factors from three case studies in aircraft maintenance - Ward, Marie (Trinity College (Dublin, Ireland). School of Psychology, 2006)
Three case studies form the heart of this thesis. The first one was based on a project called AIR, which was a human factors continuous improvement change initiative. The second one was based on a different type of change initiative called Partnership. Finally for the third the researcher developed and implemented a qualitative methodology for the diagnosis of normal organisational practice called the Role and Process Analysis (RPA).
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin